The Effect of Mind Mapping Method on The Result of Science Learning on Theme 7 Sub-Them 1 Students of Grade IV: Pengaruh Metode Mind Mapping Terhadap Hasil Belajar IPA Pada Tema 7 Subtema 1 Siswa Kelas IV - Kharizma Rizqi Amalia; Nur Efendi (Academia Open, 2022)
This study aims to improve science learning outcomes for grade IV students of SDIT Ainul Yaqin using the mind mapping method. Furthermore, this study aims to determine how much influence the mind mapping method has on the science learning outcomes of grade IV students. This study uses experimental quantitative method with One-Group Pretest-Posttest. Based on the results of the N-gain scores, as many as 8 students experienced an increase in their learning outcomes. A total of 5 students experienced an increase in grades in the high category and as many as 3 students in the medium category.With a percentage of 62.5% increase in learning outcomes in the high category and 37.5% increase in learning outcomes in the medium category. The conclusion that applying the mind mapping method in science learning on theme 7 sub-theme 1 can improve science learning outcomes for grade IV students of SDIT Ainul Yaqin. Highlights: The mind mapping method significantly improved science learning outcomes for grade IV students at SDIT Ainul Yaqin. The majority of students showed an increase in learning outcomes, with 62.5% in the high category and 37.5% in the medium category. The study employed an experimental quantitative method, specifically the One-Group Pretest-Posttest design, to assess the impact of the mind mapping method. Keywords: mind mapping method, science learning outcomes, grade IV students, SDIT Ainul Yaqin, experimental quantitative method.